2007
DOI: 10.1097/01.pcc.0000269408.64179.ff
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury in pediatric intensive care in Australia and New Zealand–A prospective, multicenter, observational study*

Abstract: ALI in children is uncommon but has a high mortality rate. Risk factors for mortality are easily identified. Ventilatory variables and indexes of lung severity were significantly associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
244
8
20

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(293 citation statements)
references
References 42 publications
(35 reference statements)
21
244
8
20
Order By: Relevance
“…Other several pediatric investigators have demonstrated stronger associations between OI and mortality for each day the patient remains on mechanical ventilation 53,54 . Data from two pediatric studies 11,55 suggested that OI may have better discriminatory value for mortality than PaO 2 / FiO 2 , and the relationship between OI and mortality strengthens as the patient remains on mechanical ventilation for the first 3 days 55 .…”
Section: Volume 59 • Number 2 Hfo Versus CMV In Pediatric Ardsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other several pediatric investigators have demonstrated stronger associations between OI and mortality for each day the patient remains on mechanical ventilation 53,54 . Data from two pediatric studies 11,55 suggested that OI may have better discriminatory value for mortality than PaO 2 / FiO 2 , and the relationship between OI and mortality strengthens as the patient remains on mechanical ventilation for the first 3 days 55 .…”
Section: Volume 59 • Number 2 Hfo Versus CMV In Pediatric Ardsmentioning
confidence: 99%
“…Reasons for that large variation may include major differences in demographics and healthcare delivery systems 9 . In pediatrics, the prevalence of ARDS is 2-12.8 per 100,000 person years [10][11][12] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although pediatric data are only observational, [34][35][36] it is important to review the recent publication by Amato et al 12 describing the association between the driving pressure and survival in adults with ARDS. Among ventilation parameters, the drive pressure (difference between peak inspiratory pressure and positive end-expiratory pressure) was most strongly associated with survival.…”
Section: Lung-protective Ventilationmentioning
confidence: 99%
“…22 The use of HFOV in pediatric critical care varies between 3% and 30% of all ventilated children. [23][24][25][26][27] This relatively low use may be explained by several factors. First, lack of equipment or disbelief of the attending physician because of the absence of sound evidence of effect.…”
Section: Introductionmentioning
confidence: 99%